Comparison of left ventricular deformation abnormalities by echocardiography with cardiac magnetic resonance imaging in patients with acute myocarditis and preserved left ventricular ejection fraction - Kandels, Joscha; Richter, Sarah; Hagendorff, Andreas; Kragholm, Kristian; Tayal, Bhupendar; Laufs, Ulrich; Denecke, Timm; Stöbe, Stephan (Frontiers in Cardiovascular Medicine, 2024)
Purpose Cardiac magnetic resonance imaging (cMRI) represents the gold standard to detect myocarditis. Left ventricular (LV) deformation imaging provides additional diagnostic options presumably exceeding conventional transthoracic echocardiography (TTE). The present study aimed to analyze the feasibility to detect myocarditis in patients (pts) with preserved LV ejection fraction (LVEF) by TTE compared to cMRI. It has been hypothesized that the number of pathological findings by deformation imaging correspond to findings in cMRI. Methods and results Between January 2018 and February 2020 102 pts with acute myocarditis according to the modified Lake Louise criteria and early gadolinium enhancement (EGE) by cMRI were identified at the department of cardiology at the University Hospital Leipzig. Twenty-six pts were included in this retrospective comparative study based on specific selection criteria. Twelve pts with normal cMRI served as a control group. LV deformation was analyzed by global and regional longitudinal strain (GLS, rLS), global and regional circumferential and radial strain (GCS, rCS, GRS, rRS), and LV rotation (including layer strain analysis). All parameters were compared to findings of edema, inflammation, and fibrosis by cMRI according to Lake Louise criteria. All pts with acute myocarditis diagnosed by cMRI showed pathological findings in TTE. Especially rCS and LV rotation analyzed by regional layer strain exhibit a high concordance with pathological findings in cMRI. In controls no LV deformation abnormalities were documented. Mean values of GLS, GRS, and GCS were not significantly different between pts with acute myocarditis and controls. Conclusion This retrospective analysis documents the feasibility of detecting regional deformation abnormalities by echocardiography in patients with acute myocarditis confirmed by cMRI. The detection of pathological findings due to myocarditis requires the determination of regional deformation parameters, particularly rCS and LV rotation. The assessment of global strain values does not appear to be of critical value.